Structuration to Research in Information Systems - Andrade, Jesús Alberto (Opción)
<!–[if gte mso 9]> Normal 0 21 false false false ES-VE X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0; @font-face font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1610611985 1073750139 0 0 159 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; text-align:justify; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-fareast-language:EN-US; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-fareast-language:EN-US; .MsoPapDefault mso-style-type:export-only; text-align:justify; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 80.4pt 70.85pt 63.8pt; mso-header-margin:35.4pt; mso-footer-margin:35.4pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Information and communications technologies cannot be studied in isolation from their social contexts. Structuration is a theory that has been in the information systems field; it might be a promising avenue to better understand how technologies interact within organizations. Because technology and information systems cannot usefully be studied in isolation from their social contexts, this paper analyzes how Giddens”™ Structuration Theory is used to offer a theoretical understanding between technology and information systems, and organizational structure and social practices. The idea being that social systems and information systems and technologies are structures that adapt well to strengthen the role of human beings as actors within the organizations.